Identification of Lifestyle Factors in Financial Literacy Using PLS-SEM Approach - Kurniawan, Novian Candra; Ni'matuzzuriyah, Ni'matuzzuriyah; Idris, Idris (Jurnal Pendidikan Ekonomi, 2025)
Financial literacy is the foundation in achieving a financially prosperous life. The role of self-control in providing control over an increasingly prestigious lifestyle, of course, will require financial literacy skills. This study aims to provide an overview using an explanaotry quantitative approach. The main data in this study were taken using a questionnaire distributed to students at SMP 11 Malang as many as 85 samples. Data processing uses the help of SMART-PLS statistical applications and the structural equation model-partial least square approach. Of the three direct tests, two hypotheses were accepted and one hypothesis was rejected. Self-control variables do not have a positive and significant effect on financial literacy. However, the self-control variable on lifestyle and lifestyle variables on financial literacy have a positive and significant effect. Then, the indirect test provides findings that lifestyle fails to mediate the relationship between self-control and financial literacy. The findings in this study indicate that the lack of self-control in students has an impact on the lack of financial literacy skills. Then, self-control has a positive and significant relationship with lifestyle. Thus, despite the increasingly prestigious lifestyle, students at SMP 11 Malang still have financial literacy skills.